The Influence of Education Funding Management and Learning Facilities on Madrasah Quality - Virgin Sabrina El-Islamy; Samsul Susilawati; Munirul Abidin (EDUCARE: Jurnal Ilmu Pendidikan, 2023)
This study aims to analyze the influence of educational financing management and learning facilities on the quality of madrasahs. This study uses a quantitative approach with data collection techniques through questionnaires, interviews, and documentation. Data analysis was carried out using multiple linear regression with the help of SPSS software. The research sample involved 40 teachers who were selected randomly. The results of the study showed that simultaneously, financing management and learning facilities had a significant effect on the quality of madrasahs, with a contribution of 39.7%. Partially, learning facilities had a significant effect on school quality (p = 0.032), while financing management did not have a significant effect partially (p = 0.228). The coefficient of determination indicated that 15.8% of madrasah quality was influenced by other variables outside the model. The implications of this study indicate the importance of optimizing the management of educational funds and providing and maintaining adequate learning facilities in supporting the improvement of madrasah quality. These results can be a strategic reference for principals, financial managers, and policy makers in designing more accountable and quality-oriented education policies.